Fluorescence of isatin N‐phenylsemicarbazones: aggregation and hydrazide–hydrazonol tautomerism. (12th February 2015) - Cigáň, Marek; Jakusová, Klaudia; Donovalová, Jana; Filo, Juraj; Horváth, Miroslav; Gáplovský, Anton
Abstract : The solution behavior of isatin N ‐phenylsemicarbazones and their interaction with anions was investigated using fluorescence technique. Existence of associate/hydrazide (keto)/hydrazonol (enol) tautomeric equilibrium explains the solvent, concentration and excitation/emission effect on fluorescence of studied compounds. Both static and dynamic fluorescence measurements, together with quenching experiments, confirm the dynamic equilibrium between individual tautomeric forms with different emissive character in solution. Because of the nonfluorescent character of hydrazonol tautomer, the quantitative description of tautomeric equilibrium anddimerization was performed using UV–Vis spectroscopy. Determined apparent association constants K ass for interaction with F − anion using Stern–Volmer plots correlate well with the previously determined sensor sensitivity. Their high values indicate again the most acidic urea NH groupdeprotonation and not the hydrogen bonded sensor : hydrazonol 1:1 complex formation. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The solution behavior of isatin N ‐phenylsemicarbazones and their interaction with anions was investigated using fluorescence technique. Both static and dynamic fluorescence measurements, together with quenching experiments, confirm the dynamic equilibrium between individual tautomeric forms with different emissive character in solution.